Targeting PD-L1 (Programmed death-ligand 1) and inhibiting the expression of IGF2BP2 (Insulin-like growth factor 2 mRNA-binding protein 2) affect the proliferation and apoptosis of hypopharyngeal carcinoma cells. Issue 1 (1st January 2021) - Yang, Xudong; Liu, Jisheng
ABSTRACT: Programmed cell death-ligand 1 (PD-L1) have been attracting increasing attention in cancer diagnosis and treatment. The insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) is involved in the progression of multiple types of cancer. So, the role of IGF2BP2 and PD-L1 in hypopharyngeal carcinoma was assessed. Western blotting and immunochemistry were used to evaluate the expression of IGF2BP2 and PD-1/PD-L1. IGF2BP2 expression was knocked down in FaDu cells, and the effects on cell viability, apoptosis and proliferation were measured. A tumor-bearing nude model of hypopharyngeal carcinoma was constructed to evaluate the effect of a PD-L1 inhibitor and IGF2BP2 knockdown on hypopharyngeal carcinoma in vivo . RNA pull-down assays were used to assess the interaction between IGF2BP2 and PD-L1. The results showed that knockdown of IGF2BP2 inhibited FaDu cell proliferation and promoted apoptosis, as evidenced by the lower cell viability, a higher ratio of TUNEL-positive cells, decreased expression of Bcl-2 and cyclins, and increased expression of cleaved-caspase 3. In vivo, the tumor volume and weight were reduced by both the PD-L1 inhibitor and IGF2BP2 knockdown. Additionally, the interaction between PD-L1 and IGF2BP2 was confirmed. In conclusion, the results in the present study revealed that inhibition of IGF2BP2 might be a potentially relevant method for treating hypopharyngeal carcinoma, and the effects might be mediated via inhibition of the PD-1/PD-L1 axis.